Penerapan Model Pembelajaran Inquiry untuk Meningkatkan Self Regulated dan Hasil Belajar Matematika Siswa Kelas VIII di SMPN 4 Jonggat - damayanti, Ema Junia; Ahmad Muzaki; Masjudin, Masjudin (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2024)
This research aims to improve self-regulated learning and mathematics learning outcomes for class VIII students at SMPN 4 Jonggat by applying the inquiry learning model. This research was conducted in two cycles, with research subjects in cycle I being 20 students and in cycle II being 17 students out of a total of 22 students. The application of the inquiry learning model to Circle material in class VIII shows an increase in self-regulation or learning independence and student learning outcomes. The research results showed an increase from cycle I to cycle II, where the average self-regulated or independent learning of students in cycle I was 51.75 in the medium category, increasing to 76.24 in the good category in cycle II. In addition, the evaluation test results showed an average increase from 65.75 in cycle I to 87.95 in cycle II. Thus, the application of the inquiry learning model in the mathematics subject Circle material is effective in improving self-regulation or learning independence and the learning outcomes of class VIII students at SMPN 4 Jonggat.